Pengujian Aplikasi Monitoring Santri Berbasis Web Pada PondokPesantren Al-Azhar Muncar Dengan Pendekatan Integration Testing - Febriana, Irma Dwi; Umam, Khoirul; Haq, Endi Sailul; Suardinata, I Wayan; Suwardiyanto, Devit (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Al-Azhar Islamic Boarding School is located in Muncar District, Banyuwangi Regency. So far, the Islamic boarding school has only been able to convey information on the students' progress to parents when collecting report cards at the end of the semester, this is considered less than optimal in terms of supervision of the students. To overcome this problem, a web-based student monitoring application has been developed which aims to make it easier to convey information to student guardians. Integration testing is carried out to ensure that every feature in the application can be connected properly. Features tested include violations, permissions, absences, and grades features, to ensure they can function properly simultaneously in their absence bug or data errors. This test is carried out to ensure that the connected features can work optimally, so that the data produced valid and reduce the potential for errors in conveying information. Testing carried out on 24 scenarios showed results with an effectiveness level of 100%, with all features declared to have passed the test. This proves that the integration between features in the application can run well.